2020
DOI: 10.1111/1749-4877.12507
|View full text |Cite
|
Sign up to set email alerts
|

First live sighting of Deraniyagala's beaked whale (Mesoplodon hotaula) or ginkgo‐toothed beaked whale (Mesoplodon ginkgodens) in the western Pacific (South China Sea) with preliminary data on coloration, natural markings, and surfacing patterns

Abstract: Beaked whales represent around 25% of known extant cetacean species, yet they are the least known of all marine mammals. Identification of many Mesoplodon species has relied on examination of a few stranded individuals. Particularly, the ginkgo-toothed beaked whale (Mesoplodon ginkgodens) and Deraniyagala's beaked whale (Mesoplodon hotaula) are among the least-known of beaked whale species, without confirmed sightings of living individuals to date. We present a sighting of 3 free-ranging individuals of M. gink… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 31 publications
(73 reference statements)
1
13
1
Order By: Relevance
“…Although the observed animals may exhibit a geographic variation of the color patterns of ginkgo‐toothed or Deraniyagala's beaked whales and we cannot rule out either species, their external features do not match any published descriptions of these species. Superficially, the whales we saw closely resemble a group of Mesoplodon beaked whales (described as either M. ginkgodens or M. hotaula ) photographed recently in the South China Sea (Rosso et al, 2020) but differ in the shape of the cheek patch and the presence of dark pigmentation below the tooth in the male.…”
Section: Figuresupporting
confidence: 56%
“…Although the observed animals may exhibit a geographic variation of the color patterns of ginkgo‐toothed or Deraniyagala's beaked whales and we cannot rule out either species, their external features do not match any published descriptions of these species. Superficially, the whales we saw closely resemble a group of Mesoplodon beaked whales (described as either M. ginkgodens or M. hotaula ) photographed recently in the South China Sea (Rosso et al, 2020) but differ in the shape of the cheek patch and the presence of dark pigmentation below the tooth in the male.…”
Section: Figuresupporting
confidence: 56%
“…The sperm whale ( Physeter macrocephalus ) was encountered twice (10 individuals), whereas Risso's dolphins ( Grampus griseus , 12 individuals), Cuvier's beaked whales ( Ziphius cavirostris , 2 individuals), and an unidentified beaked whale (either the ginkgo‐toothed beaked whale, Mesoplodon ginkgodens , or Deraniyagala's beaked whale, Mesoplodon hotaula ; identification details see Rosso et al . 2020) were recorded only once each. The species accumulation curves, which did not reach an asymptote, are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 8 encountered species, 7 were recorded at sea in the northern South China Sea for the first time. Through using photographic data, Rosso et al (2021) identified a group of mysterious beaked whales from the field survey depicted by Lin et al (2021a). Photographic evidences showed that the mysterious beaked whales are either ginkgo-toothed or Deraniyagala's beaked whales (Mesoplodon ginkgodens or M. hotaula).…”
Section: Multiple-species Field Surveysmentioning
confidence: 99%
“…Through using photographic data, Rosso et al . (2021) identified a group of mysterious beaked whales from the field survey depicted by Lin et al . (2021a).…”
Section: Ecology and Behaviormentioning
confidence: 99%